CROSS-CULTURAL STUDY OF FINANCIAL DECISIONS MAKING BY UKRAINIAN AND CHINESE STUDENTS - Павленко, Валентина Миколаївна; Кислиця, Аліна Костянтинівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article identifis 6 the main potential strategies for making fiancial decisions - «maximum selfihness», «moderate selfihness «, «equalization», «altruism without loss to oneself», «maximum altruism» and «unformed» strategies - and shows the way of their empirical study. It is shown that the most widespread strategy among all students is the «equalization strategy», the « strategy of maximal selfihness» is less widespread, and the least widespread strategy is «altruism without loss to oneself». It is proved that the strategy of «maximum selfihness» prevails among Ukrainian students, and in the Chinese students - an “equalization strategy”. Relationships between strategies for making fiancial decisions, level of national identity, jealousy and collectivism-individualism are investigated. It has been found that fiancial decision making strategies are statistically signifiantly correlated only with the level of national identity and, moreover, in each of the studied national groups these connections have their own specifiity: in the group of Ukrainian students there is a positive link between the level of national identity and the «strategy of moderate selfihness», and in the group of Chinese students - a positive link between the level of national identity and the «equalization strategy». This means that the more students consider themselves to be representatives of their nationality, the more the «strategy of moderate selfihness» prevails among Ukrainian students, and the «equalization strategy» among the Chinese students.